POLICIES AND STRATEGIES AIMED AT ENSURING THE SECURITY OF BANKING INSTITUTIONS AND THEIR IT SYSTEMS - Marinela Adriana Butcovan; Rica Ivan (Agora International Journal of Economical Sciences (AIJES), 2023)
With the development of the banking system, its security and, implicitly,security polic ies emerged as cr itical factors in the entire banking s ector . In the context of thecurrent technological development, the vulnerability of banking institutions has increaseddramatically . For both bank employee s and customer s , cybersecurity, operational securityand data privacy have become top priorities. Th erefore , a central concern for banks is theprompt detection of threats and the development of measures aimed ateliminat ing such dangers , which might both considerably increas e the level of security in thebanking sector.
Keywords: 330